2021
DOI: 10.3892/ol.2021.13060
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA ATAD1 is upregulated in acute myeloid leukemia and promotes cancer cell proliferation by downregulating miR‑34b via promoter methylation

Abstract: A previous study has reported the oncogenic role of circular RNA (circ)-ATAD1 in gastric cancer. The aim of the present study was to investigate the role of circ-ATAD1 in acute myeloid leukemia (AML). Bone marrow mononuclear cells were collected from 60 patients with AML and 60 healthy controls, followed by RNA isolation and reverse transcription-quantitative PCR to assess the expression of circ-ATAD1 and microRNA (miR)-34b. A subcellular fractionation assay was used to determine the subcellular location of ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Our previous studies confirmed that Thorase plays a vital role in removing misplaced α-synuclein from the outer membrane of mitochondria and plays a protective role in neurodegeneration mediated by α-synuclein [ 33 ]. Recently, several research groups have found that circRNA circ-ATAD1 (Thorase) plays a vital role in both solid tumors (such as gastric cancer, colorectal cancer and endometrial cancer) [ 46 , 47 , 48 ] and blood tumors (such as acute myeloid leukemia) [ 49 ]. Multi-omics results showed that downregulation of ATAD1 was a clinical biomarker for the pathological diagnosis and prognosis of prostate adenocarcinoma patients [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies confirmed that Thorase plays a vital role in removing misplaced α-synuclein from the outer membrane of mitochondria and plays a protective role in neurodegeneration mediated by α-synuclein [ 33 ]. Recently, several research groups have found that circRNA circ-ATAD1 (Thorase) plays a vital role in both solid tumors (such as gastric cancer, colorectal cancer and endometrial cancer) [ 46 , 47 , 48 ] and blood tumors (such as acute myeloid leukemia) [ 49 ]. Multi-omics results showed that downregulation of ATAD1 was a clinical biomarker for the pathological diagnosis and prognosis of prostate adenocarcinoma patients [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute myelogenous leukemia (AML) is a highly aggressive malignancy of hematopoietic stem cells. A series of studies have shown that circRNAs are aberrantly expressed in AML ( Chang et al, 2022 ; Wu et al, 2021 ). Sun et al (2019) demonstrated that there was a trend of elevated expression of circMYBL2 in AML patients with an FLT3-ITD mutation.…”
Section: Survey Methodologymentioning
confidence: 99%
“…Leukemia, particularly acute myelogenous leukemia (AML), is a widespread and challenging form of acute leukemia that accounts for approximately 80% of all cases worldwide [125]. In chronic lymphocytic leukemia (CLL), a regulatory circuit has been discovered.…”
Section: The Role Of Mir-34s In Leukemiamentioning
confidence: 99%